Metagenomic research of infectious diseases in archaeological contexts: evidence from the Hospital Real de Todos-os-Santos (Portugal) - Alves-Cardoso, Francisca; Palomo-Díez, Sara; Alonso Conde, Alejandro; Gomes, Cláudia; Casimiro, Silvia; Banha da Silva, Rodrigo; Arroyo-Pardo, Eduardo (MDPI, 2022)
Syphilis is one of the most exciting diseases explored in paleopathology and, therefore, tracing back its origin and development has provided a prolific debate. The combination of paleopathological data with historical sources, iconography, and archaeological contexts were the primary sources used to reconstruct its historical path. However, there are some limitations to paleopathological diagnosis due to the nature of bone reaction to stimuli. In addition, historical sources are subjected to a bias of social and cultural nature and the knowledge of those who wrote them. Hence, ancient DNA analysis offers the possibility of acquiring proof of cause by identifying pathogens in an organism. We undertook a metagenomic study of a skeleton exhumed from the Royal Hospital of All Saints (Portugal), renowned for treating syphilis from the 16th century onwards. The skeleton had previously been diagnosed with syphilis according to paleopathological analysis. However, the metagenomics analysis showed no presence of the pathogen associated with syphilis (i.e., Treponema pallidum) but revealed pathogenic microorganisms related to respiratory diseases (pneumonia), nonspecific bone infections (osteomyelitis), and oral bacterial pathologies as well as Hansen’s disease (also known as leprosy). The results are exciting and demand a reappraisal of the observed bone changes, recontextualizing their characterization as syphilis related. They prove that past reconstruction of health and disease diagnoses based on assessing human osteological remains of known context (such as a syphilitic hospital) may bias interpretations and, therefore, caution is recommended, not forgetting that the absence of evidence is not evidence of absence (in this case of syphilis) in life.
Keywords: ancient DNA; 16S metagenomics; microbiome; paleopathology; leprosy; syphilis; bones; human remains